2018
DOI: 10.14423/smj.0000000000000831
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound Needs Assessment, Curriculum Design, and Curriculum Assessment in a Large Academic Internal Medicine Residency Program

Abstract: We used a needs assessment to guide the development of a longitudinal, multidisciplinary POCUS curriculum. Residents who completed all components showed substantial long-term gains in knowledge in all major applications and high use of and confidence in cardiac and pulmonary applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 12 publications
4
40
1
Order By: Relevance
“…They similarly reported frequent POCUS utilization in clinical practice that was out of proportion to self‐reported confidence in skill level. Their study also found that most residents did not feel adequately supervised when using POCUS on the medicine wards 18 . While we did not directly ask about supervision in our survey, trainees in our survey frequently cited lack of just‐in‐time expert feedback as a barrier.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…They similarly reported frequent POCUS utilization in clinical practice that was out of proportion to self‐reported confidence in skill level. Their study also found that most residents did not feel adequately supervised when using POCUS on the medicine wards 18 . While we did not directly ask about supervision in our survey, trainees in our survey frequently cited lack of just‐in‐time expert feedback as a barrier.…”
Section: Discussionmentioning
confidence: 81%
“…To meet the rapid growth of POCUS utilization, several professional societies have published guidelines, consensus statements, or expert opinions detailing recommendations for POCUS application in both adults and children 10‐17 . However, incorporation of these guidelines into GME training programs is variable and limited 18‐21 . Furthermore, many providers completed their GME training prior to incorporation of POCUS educational goals into GME program requirements yet still desire POCUS training.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this research demonstrated an effective way to increase the performance and favorable attitudes of bedside ultrasound in residents. Anstey et al demonstrated an effective PoCUS curriculum for internal medicine residents that produced long-term gains in knowledge and high con dence achievements [26]. Emergency medicine residents struggle in overcrowded emergency departments to manage various patients with severe needs, which results in a stressed and dissatis ed training period [27,28], which often leads residents to overload themselves to complete the mandatory ultrasound practice off duty.…”
Section: Discussionmentioning
confidence: 99%
“…Point of care ultrasound (POCUS) refers to the use of ultrasound by the treating provider at the bedside to answer focused clinical questions. The use of POCUS has become increasingly popular within the field of Internal Medicine (IM) worldwide [1][2][3][4][5]. In settings where material and human resource constraints limit the availability of many diagnostic modalities, POCUS is a particularly valuable tool [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Steven Fox, MD 1 ; Michelle Fleshner, MD MPH 1 ; Collin Flanagan, DO 2 ; Thomas Robertson, MD 2 ; Ayako Wendy Fujita, MD 1 ; Divya Bhamidipati, MD 1 ; Abdulrahman Sindi, MD 3 ; Raghunandan Purushothaman, MD 1 ; Thuy Bui, MD 1 (1) University of Pittsburgh Medical Center, Presbyterian. Internal Medicine.…”
mentioning
confidence: 99%